2020
DOI: 10.21037/tau.2020.01.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Comprehensive Complication Index and Clavien-Dindo systems in predicting perioperative outcomes following radical nephroureterectomy

Abstract: Background: Complications can occur following radical nephroureterectomy (RNU) in 20-40% of patients. The Comprehensive Complication Index (CCI) is an alternative grading system to the Clavien-Dindo (CD) grading system that aggregates all complications experienced by a patient on a continuous (as opposed to categorical) scale. We investigate whether the cumulative nature of CCI renders it superior to CD in predicting perioperative course after RNU. Methods:The records of 596 patents who underwent RNU at 7 acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…In our study, a total number of 106 (106/194, 54.6%) suffered from a perioperative complication according to CDC (I-V). Compared to complication rates of other studies, ranging from 20 to 50% [19][20][21][22], our overall com-plication rate meets the upper margin, most likely because of an older patient clientele due to being a referral center. Complications were significantly increased in the eldest cohorts 3 (80-84 years) and 4 (≥85 years) with complication rates of 92.6% and 87.5%, respectively, compared to cohorts 1 (43.4%) and 2 (56.1%).…”
Section: Discussioncontrasting
confidence: 65%
“…In our study, a total number of 106 (106/194, 54.6%) suffered from a perioperative complication according to CDC (I-V). Compared to complication rates of other studies, ranging from 20 to 50% [19][20][21][22], our overall com-plication rate meets the upper margin, most likely because of an older patient clientele due to being a referral center. Complications were significantly increased in the eldest cohorts 3 (80-84 years) and 4 (≥85 years) with complication rates of 92.6% and 87.5%, respectively, compared to cohorts 1 (43.4%) and 2 (56.1%).…”
Section: Discussioncontrasting
confidence: 65%
“…For example, a lower incidence of complications was observed in a study because only urological complications with ≥ grade III were included to analyze as the study parameters. [ 26 ] While, a much higher overall incidence of complication was presented in another study owing to the inclusion of many minor complications with grade I to II. [ 27 ] These deviations in the selection and definition of complications frequently appeared in many literature reports, so how to identify and involve grade I to II still requires to be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that severe complications occurred in 17%,25 however, they did not describe the associations between Clavien-Dindo classification or CCI with surgical outcomes. Studies of non-gynecological surgery have shown that the increasing severity of CCI was associated with intensive care unit admission, prolonged length of hospital stay, and readmission after surgery 14 26 27. A study of major abdominal surgery (n=206) reported the median CCI of 20.9 points (range 0–44.9) and Clavien-Dindo classification grade 2 complications were the most common.…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic-based system greatly facilitated a standardized and reproducible measurement of post-operative complications. As a result, it is accepted in surgical fields and additionally validated by the European Association of Urology as a standard classification for evaluating post-operative complications for urological surgeries 14. Nevertheless, the Clavien-Dindo classification has limitations, especially in patients with multiple complications.…”
Section: Introductionmentioning
confidence: 99%